Digital Engagement Strategy: An Analysis of Promotional Content on Instagram Accounts @arpesalibrary01_ and @perpustakaan_mastripkab.kediri - Ayumastika Ningrum (Journal of Digital Scholarship in Archives and Information, 2026)
Background: Libraries use social media as a promotional medium to increase public awareness regarding the importance of libraries as centers of learning, intellectual development, and entertainment. Instagram has become one of the most widely used platforms for promoting library services, activities, and collections to users. Effective promotional strategies are needed to attract user attention and increase library engagement.Aims: This study aims to compare the use of the Instagram accounts @arpesalibrary01_ and @perpustakaan_mastripkab.kediri as promotional media for library users.Methods: This study employed a qualitative method with a descriptive research design. Data were collected through observation of the Instagram accounts. The analysis was based on Philip Kotler’s (2016) theory regarding four promotional element indicators: promotional messages, promotional media, promotional timing, and promotional frequency.Results: The results showed that the Instagram account @perpustakaan_mastripkab.kediri performed better as a promotional medium compared to @arpesalibrary01_. This finding was supported by the more complete and descriptive promotional posts, the effective use of captions, appropriate upload timing, and more consistent promotional frequency implemented by @perpustakaan_mastripkab.kediri.Conclusion: The study concludes that effective Instagram-based library promotion depends on the quality of promotional messages, consistency of posting, appropriate timing, and the use of descriptive content. Libraries that manage social media professionally and consistently are more likely to attract user attention and improve library promotion outcomes.